KREATIV OYLAW HÁM KOMMUNIKATIV KOMPETENCIYA MASHQALALARÍNÍŃ ÓZ-ARA QATNAS MÁSELESI - Abdiev, B.T. (SCIENCE and SOCIETY, 2023)
This article analyzes a number of problems of modern education. Comprehensively analyzed and made conclusions about the communicative competence and the benefits of creative thinking among students. In the system of higher education Suggestions and considerations are made related to the development of communicative competence and creative thinking.
Keywords: communicative; competence; creative; modernization; culture; society; innovation; method; system; integration; diversification